Emergency rush repair task scheduling of distribution networks in large-scale blackouts. (November 2016) - Pang, Nansheng; Liu, Hao; Huang, Shuyi; Meng, Junjiao
Highlights: Study the rush repair of distribution networks based on project scheduling theory. Propose a serial schedule generation mechanism of distribution network rush repair. Study the application of emergency generator vehicle and nearby repair strategy. Build a repair model aiming to minimize economic losses and shorten repair time. Abstract: This paper focuses on the emergency rush-repair task scheduling of distribution networks in power grid emergencies. As there are many characteristics in distribution network emergency rush-repair such as large number of rush repair points, diverse but with limited repair resources and urgent repair time, this paper takes constraint conditions, such as a variety of execution modes and repair resources into consideration during the model building process of the emergency rush repair scheduling, and we study emergency repair strategies, such as using the emergency generator vehicle, nearby repair strategy and ordinary repair strategy. In order to obtain the optimal solution and satisfy the constraints of the distribution network repair model, this paper improves the traditional serial schedule generation mechanism to a distribution network repair serial schedule generation mechanism by using improved SA algorithm and hierarchical optimization method to search the optimal solution. Finally, we use the model to an example and analyze it. It is validated that the two schedule generation mechanisms that use nearby repair strategy and ordinary repair strategy are both effective. Both the advantages and disadvantages of two mechanisms, and the feasibility and rationality of the model are analyzed in this paper.